Identification of Human Enzymes Oxidizing the Anti-Thyroid-Cancer Drug Vandetanib and Explanation of the High Efficiency of Cytochrome P450 3A4 in its Oxidation - Indra, Radek; Pompach, Petr; Martínek, Václav; Takácsová, Paulína; Vavrová, Katarína; Heger, Zbyněk; Adam, Vojtěch; Eckschlager, Tomáš; Kopečková, Kateřina; Arlt, Volker Manfred; Stiborová, Marie (International journal of molecular sciences, 2019)
The metabolism of vandetanib, a tyrosine kinase inhibitor used for treatment of symptomatic/progressive medullary thyroid cancer, was studied using human hepatic microsomes, recombinant cytochromes P450 (CYPs) and flavin-containing monooxygenases (FMOs). The role of CYPs and FMOs in the microsomal metabolism of vandetanib to N-desmethylvandetanib and vandetanib-N-oxide was investigated by examining the effects of CYP/FMO inhibitors and by correlating CYP-/FMO-catalytic activities in each microsomal sample with the amounts of N-desmethylvandetanib/vandetanib-N-oxide formed by these samples. CYP3A4/FMO-activities significantly correlated with the formation of N-desmethylvandetanib/ vandetanib-N-oxide. Based on these studies, most of the vandetanib metabolism was attributed to N-desmethylvandetanib/vandetanib-N-oxide to CYP3A4/FMO3. Recombinant CYP3A4 was most efficient to form N-desmethylvandetanib, while FMO1/FMO3 generated N-oxide. Cytochrome b5 stimulated the CYP3A4-catalyzed formation of N-desmethylvandetanib, which is of great importance because CYP3A4 is not only most efficient in generating N-desmethylvandetanib, but also most significant due to its high expression in human liver. Molecular modeling indicated that binding of more than one molecule of vandetanib into the CYP3A4-active center can be responsible for the high efficiency of CYP3A4 N-demethylating vandetanib. Indeed, the CYP3A4-mediated reaction exhibits kinetics of positive cooperativity and this corresponded to the in silico model, where two vandetanib molecules were found in CYP3A4-active center.
Keywords: Microsomes, Liver; cytochrom P-450 CYP3A; Recombinant Proteins; Piperidines; protinádorové látky; Enzymes; molekulární struktura; Molecular Structure; flavin-containing monoxygenases; vztah mezi dávkou a účinkem léčiva; tyrosine kinase inhibitor; enzymy; vandetanib; cytochromes P450; inhibitory proteinkinas; piperidiny; králíci; molekulární modely; molekulární konformace; oxidace-redukce; krysa rodu Rattus; rekombinantní proteiny; Models, Molecular; Animals; lidé; Cytochrome P-450 CYP3A; Humans; zvířata; Rats; Protein Kinase Inhibitors; Rabbits; myši; Molecular Conformation; Quinazolines; Oxidation-Reduction; Mice; chinazoliny; Dose-Response Relationship, Drug; jaterní mikrozomy; Antineoplastic Agents; metabolism